The Graduates Tracer Study: Bachelor of Elementary Education Program - Abana, Adona S.; Ramos, Andy B.; Gumarang Jr., Bernardo K.; Tarun, Jaine Z. (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
The study assessed the impact of the Bachelor of Elementary Education program in the life of its graduates in terms of their employability and professional competencies based on the perceptions of graduates and their employers. The survey method was used in the study to determine the graduates' status and performance. There are 250 BEEd graduates involved in the study. Descriptive statistics such as frequency, percent, and arithmetic mean were utilized to determine and describe the profile of graduates and employers, the trend in the employment of graduates for the term being studied, the employers’ assessment of the graduates in terms of their knowledge and understanding of their field of specialization, qualities, general skills and specialized skills generally expected of them in order to succeed in their teaching performance, and the over-all preparation of graduates acquired from the University for the type of work they are currently engaging and other skills needed for their future demands. The data generated from the employers' assessment of the variables mentioned was further analyzed and categorized to generate interrelated thoughts/themes that will emerge from the data. The results of the study showed that graduates of the program are competent because most of the graduates are licensed professionals, employed with regular or permanent status. However, it has been found that graduates need to gain innovative skills such as, research and the use of information communication and technology. The findings can be used as the basis of the program in improving the curriculum and instruction.